A Phase I/II Study of Nab-Paclitaxel, Cisplatin, and Cetuximab With Concurrent Radiation Therapy for Locally Advanced Squamous Cell Cancer of the Head and Neck. (2nd January 2017) - Chun, Stephen G.; Hughes, Randall; Sumer, Baran D.; Myers, Larry L.; Truelson, John M.; Khan, Saad A.; Ma, Tsung-Wei; Xie, Yang; Yordy, John S.; Cooley, Susan; Wu, Jean; Choy, Hak; et al.
ABSTRACT: Nab-paclitaxel might impact efficacy of radiation for head and neck (H&N) cancer. Nab-paclitaxel, cisplatin, cetuximab, and radiation were evaluated in patients with locally advanced head and neck cancer in this phase I/II trial. Median follow-up was 24 months for 34 patients. The maximum tolerated dose of nab-paclitaxel was 20 mg/m 2 with 20 mg/m 2 cisplatin and 250 mg/m 2 cetuximab. The 2-year progression-free survival (PFS) was 60% (95% confidence interval (CI) 0.42, 0.78), local control 71% (95% CI 0.55, 0.87), and overall survival 68% (95% CI 0.50, 0.86). This is the first study evaluating these agents with radiation in humans, with similar 2-year PFS as historic control.